Por uma etnopreservação integral do patrimônio: a biografia de quatro máscaras Waurá - Bruno Brulon; Leandro Guedes (Midas: Museus e Estudos Interdisciplinares)
The article presents a museological analysis of the trajectory of four masks produced by the Waurá people that were acquired by the Museu do Índio – FUNAI (Fundação Nacional do Índio) in Rio de Janeiro. It proposes the notion of an integral preservation of indigenous cultural heritage, involving the preservation of the environment and land demarcation, the indigenous participation in the museum processes as well as the procedures that constitute musealisation in its different stages, which are: selection, documentation, conservation and communication. The analysis is based on the notion according to which an object or collection can take different social statuses at different times, going through successive phases of singularisation, to become inalienable artifacts through musealisation. We propose, then, a broader perception of “preservation” as it has been adopted by museums that develop museum practices in partnership with indigenous groups. The analysis of the biographic trajectory of the Waurá masks allows the observation of how musealised indigenous objects may raise questions on the museum regimes that work for the preservation of the living. We conclude that these regimes mobilise certain criteria and values that overflow from the cultural institutions to the indigenous groups in their living territories.